Pelatihan Operator Komputer Madya Untuk Meningkatkan Keterampilan Teknologi Tenaga Pendidik Pondok Pesantren Di Kabupaten Cirebon - Ade Irma Purnama Sari; Ade Rizki Rinaldi; Ahmad Najib Yahya; Ainun Nisa Sari (CV. Multi Kreasi Media, 2023)
This Community Service Program aims to improve the technological skills of educators at Islamic boarding schools (Pondok Pesantren) in Cirebon Regency through Intermediate Computer Operator Training. The main problem faced by educators is the limited knowledge and skills in operating computers, particularly in using office applications such as Microsoft Word, Excel, and PowerPoint. This condition affects the efficiency of pesantren administration and limits the utilization of technology in the learning process. This program was carried out through several stages, including needs identification, preparation of training materials, hands-on practice, evaluation, and mentoring. The materials provided covered basic computer operation, document management, data processing, digital presentation creation, and digital data management of students. The results of the training showed a significant improvement in participants' skills, especially in using office applications and managing digital-based administration. Several pesantren have started to implement digital systems for recording student data, finances, and lesson schedules. In addition, educators are now able to create more attractive and interactive technology-based learning materials. The outputs of this activity include digital training modules, tutorial videos, evaluation reports, and the formation of a technology-based educator community. This program is expected to continue to develop so that educators in Islamic boarding schools are increasingly ready to face the challenges of digitalization in education and are able to improve the quality of administrative management and learning processes within the pesantren environment.